2019
DOI: 10.3168/jds.2019-16970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral, intravenous, and subcutaneous fluid therapy for resuscitation of calves with diarrhea

Abstract: Neonatal diarrhea remains the primary cause of mortality in dairy calves around the world, and optimal treatment protocols are needed. The main goals of therapy are to restore hydration and electrolyte concentrations, correct strong ion (metabolic) acidemia, and provide nutritional support. Administration of oral electrolyte solutions (OES) has long been the primary method used to treat neonatal diarrhea in humans and calves because OES are capable of addressing each of the primary goals of therapy. In calves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 28 publications
2
22
3
Order By: Relevance
“…Diarrhea in yaks was signi cantly higher in yak calves (Fig. 2), which was in line with the widely accepted knowledge that morbidity and mortality of diarrhea in calves is more serious [35]. Therefore, discovering the potential causes of this emerging diarrhea is urgent and meaningful, especially on the remote plateau.…”
Section: Discussionsupporting
confidence: 79%
“…Diarrhea in yaks was signi cantly higher in yak calves (Fig. 2), which was in line with the widely accepted knowledge that morbidity and mortality of diarrhea in calves is more serious [35]. Therefore, discovering the potential causes of this emerging diarrhea is urgent and meaningful, especially on the remote plateau.…”
Section: Discussionsupporting
confidence: 79%
“…The administration of ORS remains the gold standard for resuscitating diarrheic calves with moderate dehydration and acidemia ( Taylor et al, 2017 ; Doré et al, 2019 ). Worldwide, diarrhea caused by C. parvum is one of the most important diseases of young ruminant livestock, particularly in neonatal calves.…”
Section: Discussionmentioning
confidence: 99%
“…Without free water access, acute hypernatremia might be the consequence when dehydrated calves are treated with hypertonic ORS ( Kirchner et al, 2014 ; Trefz et al, 2017 ). In a recent study in calves with osmotic diarrhea, a slightly hypertonic ORS, alone and combined with intravenous hypertonic saline infusion, was superior in expanding plasma volume compared with intravenous Ringer lactate infusion ( Doré et al, 2019 ). The increase in plasma osmolality, in particular [Na + ], causes thirst and leads to higher consumption of water ( Sen et al, 2009 ; Thornton, 2010 ; Wenge et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also concern that bicarbonate may interfere with milk clotting in the abomasum as previous studies identified that OES with a bicarbonate concentration >40 mEq/L has negative effects on milk clotting (Miyazaki et al, 2019). Newer OES formulations contain acetate, propionate, and citrate, which have been shown to have similar alkalinizing effects to bicarbonate (Doré et al, 2019). They are considered bicarbonate precursors because they produce water and bicarbonate ions when metabolized.…”
Section: Short Communicationmentioning
confidence: 99%